Interdisciplinarity in Pastoral Theology. An Example of Socio-Theological Research - Szymczak, Wioletta (Verbum Vitae, 2020)
The purpose of the article is to analyze the idea of interdisciplinary research involving pastoral theology and sociology. This is one of the methodological proposals for research projects carried out under pastoral theology. Interdisciplinarity is understood as combining research methods for the cooperation of scientists from both disciplines in the process of planning, implementing and interpreting the results of empirical research. It is inspired by a problem identified in pastoral theology that requires exploration. The presentation consists of three parts. The first is devoted to the location of empirical research within pastoral theology. The second concerns the assumptions and significance of interdisciplinary research involving pastoral theologians and sociologists. In the final part, the areas of interdisciplinary cooperation among the research teams are pointed out. The potential of qualitative research as a space for cooperation among representatives of both sciences and as an important source of knowledge from the viewpoint of pastoral theology is shown. The comparative and synthetic method was used. The analysis shows that interdisciplinary research in the field of pastoral theology has great potential related to the acquisition and interpretation of multi-faceted empirical data and the designation of new research fields, which will significantly enrich the theological analysis process as well as the presentation and application of pastoral models.